An evaluation of the impact of FIFA World Cup on soccer emergency department injuries among Montreal adolescents - Keays, Glenn; Friedman, Debbie; Beaudin, Marianne; Gagnon, Isabelle (Journal of paediatrics and child health, 2018)
Aim The ‘trickle‐down effect’, or how major sports events have a positive impact on sports participation, has been the subject of many studies, but none produced conclusive results. We took a different approach and rather than look at sports participation, we used injuries as a proxy and see if injuries increased, or remained the same, after the International Federation of Association Football World Cup. Methods Using a retrospective cohort design, we looked at the injuries suffered by males and females (13–16 years old) while playing team sports in Montreal, that occurred in May to July, from 1999 to 2014. Information reported by the Canadian Hospitals Injury Reporting Prevention Program (CHIRPP) was limited to the two CHIRPP centres in Montreal: the Montreal Children's Hospital and Hopital Sainte‐Justine. Results In females, no significant trends were noticed. In males who played non‐organised soccer, the percent changes between FIFA World Cup (WC) (June) and pre‐FIFA WC (May) was always highest during FIFA WC years: 17.2% more injuries in years when FIFA WC was held compared to 1.3% less injuries during non‐FIFA WC years. In non‐organised soccer, male players suffered less strains/sprains (11.9% vs. 30.1%; P = 0.015), suffered more severe injuries (59.7% vs. 43.1%; P = 0.049) and more of their injuries were the results of direct contact with another player (26.8% vs. 13.3%; P = 0.028) during FIFA WC. Conclusion FIFA WC seems to have an impact on the injuries of teenage boys when playing non‐organised soccer. The impact was short‐lived, only lasting during the FIFA WC event.